Antibacterial, antioxidant and cytotoxic studies of total saponin, alkaloid and sterols contents of decoction of Joshanda: Identification of components through thin layer chromatography. (March 2015) - Khan, Haroon; Khan, Murad Ali; Abdullah,
The current study was aimed to assess antibacterial, antioxidant and cytotoxic activity of total saponin, alkaloid and sterol contents of Joshanda decoction followed by its constituent's analysis via thin layer chromatography (TLC). Saponins and alkaloids showed prominent antibacterial activity against Staphylococcus aureus, Bacillus subtilis, Bacillus cereus and Klebsiella pneumoniae whereas sterols only against S. aureus . Saponin and alkaloid contents of 97 and 108 µg/ml, respectively, showed prominent free radical scavenging activity against 1, 1-diphenyl-2-picrylhidrazyl, with mild cytotoxicity in brine shrimp cytotoxic test. Under ultraviolet light at 254 nm, TLC of total saponins showed eight different compounds, total sterols comprising three while total alkaloids two compounds of various polarities. It is concluded that the various contents of Joshanda decoction possess outstanding susceptibility against bacteria implicating primarily upper respiratory tract infections augmented by strong antioxidant activity.